High performance motor control system with fast response dynamic performance - Mah, Javiar Hao Xuan (Nanyang Technological University, 2024)
The rise in the demand for high performance application across many industries such as in train drive system, electric-assisted turbocharge and even 3D printer, have prompted the use of permanent magnet synchronous motor (PMSMs). This is mainly due to its numerous advantages such as high efficiency, small size, and precise control over other types of electric motors. The traditional PI controller commonly utilizes to control PMSMs due to its ease of implementation, struggles to meet the high-performance requirements of fast response and low overshoot simultaneously. In this study, the limitation of the PI controller will be discussed, and alternative control strategies and optimisation algorithms will be proposed. The alternative control strategies are: Fractional Order Proportional Integral (FOPI) controller and Deadbeat controller (DBCC). Through Genetic Algorithms (GA) optimisation, MATLAB simulation of the different controllers will be conducted. The effectiveness of the controller in achieving high performance will be evaluated using a few key factors such as response time, overshoot derived from the speed and torque graph. To further determine the effectiveness of the controller, a 5 Nm external torque will be introduced at t = 0.15 s to evaluate its recovery performance. To carry out the simulation, a model of the PMSM with the controllers will be built. The main block of the PMSM and the SVPWM remains the same throughout the experiment, changing only the type of controller or the controller gains value. The reference speed will also be kept the same at 1000 rpm. Through GA optimisation process, the speed and torque response graph will be recorded and be compared to evaluate their performance. The use of FOPI as a speed controller and DBCC produced the best performance in terms of lowering the overshoot and increasing the responsiveness of the system compared to the traditional PI controller, PI with GA optimisation and FOPI with GA optimisation.